2018
DOI: 10.1111/jvh.12823
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of hepatitis C virus cure: Every rose has thorns

Abstract: To examine mid-term benefits on hepatic complications, extrahepatic clinical syndromes and quality of life associated with HCV cure; to review the few safety issues linked to oral direct-acting antivirals (DAAs); and to discuss the potential population benefits of reducing the burden of HCV infection. DAAs cure HCV infection in more than 95% of patients. The halting of liver inflammation and fibrosis progression translates into both hepatic and extrahepatic benefits and reduces the need for liver transplantati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 75 publications
0
7
1
1
Order By: Relevance
“…In a retrospective cohort study, it was found that Beck Depression Inventory scores improved with sofosbuvir-based treatment (29). DAAs are supposed to reduce extrahepatic manifestations such as fatigue and depression by reducing the systemic inflammation and immune activation secondary to HCV replication (30). However, in our study, we did not observe an improvement in depression or anxiety scores.…”
Section: Discussioncontrasting
confidence: 81%
“…In a retrospective cohort study, it was found that Beck Depression Inventory scores improved with sofosbuvir-based treatment (29). DAAs are supposed to reduce extrahepatic manifestations such as fatigue and depression by reducing the systemic inflammation and immune activation secondary to HCV replication (30). However, in our study, we did not observe an improvement in depression or anxiety scores.…”
Section: Discussioncontrasting
confidence: 81%
“…10 Early treatment of infected individuals is needed to reduce the risk of hepatocellular carcinoma occurrence. 9 The results of the present study show that liver cancer currently represents the main cause of death among decedents with any mention of HCV infection.…”
Section: Discussionmentioning
confidence: 53%
“…In Italy, treatment with DAA was initially restricted to patients with advanced liver disease, and thereafter, the indication for treatment moved to the less severe stages . Early treatment of infected individuals is needed to reduce the risk of hepatocellular carcinoma occurrence . The results of the present study show that liver cancer currently represents the main cause of death among decedents with any mention of HCV infection.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations